2019
DOI: 10.1016/j.ajog.2018.11.417
|View full text |Cite
|
Sign up to set email alerts
|

396: Medication adherence in women with gestational diabetes and its effect on pregnancy outcomes

Abstract: OBJECTIVE: Treatment of gestational diabetes (GDM) is associated with improved pregnancy outcomes. Obstacles to taking prescribed medications can lead to non-compliance. The objective was to determine the challenges that lead to low medication adherence and whether this increases the rate of adverse pregnancy outcomes in women with GDM. STUDY DESIGN: A prospective, observational study was performed of women with GDM treated with metformin, glyburide or insulin at a tertiary care center. Women greater than 16 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As with all treatment, adherence to the advice given is key [ 3 ]. Among women with GDM, moderate adherence has been reported for the dietary and pharmacological recommendations, including oral hypoglycaemics and insulin [ 4 , 5 ]. Some studies have found an association between achieving the appropriate gestational weight gain and high adherence to pharmacological guidelines for the management of GDM and improved pregnancy health outcomes [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As with all treatment, adherence to the advice given is key [ 3 ]. Among women with GDM, moderate adherence has been reported for the dietary and pharmacological recommendations, including oral hypoglycaemics and insulin [ 4 , 5 ]. Some studies have found an association between achieving the appropriate gestational weight gain and high adherence to pharmacological guidelines for the management of GDM and improved pregnancy health outcomes [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among women with GDM, moderate adherence has been reported for the dietary and pharmacological recommendations, including oral hypoglycaemics and insulin [ 4 , 5 ]. Some studies have found an association between achieving the appropriate gestational weight gain and high adherence to pharmacological guidelines for the management of GDM and improved pregnancy health outcomes [ 5 , 6 ]. Infants of women with high adherence to pharmacological treatments for GDM had lower rates of neonatal hypoglycaemia compared to infants of women with low adherence [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation